Cobitis xui, a new species of spined loach (Teleostei: Cobitidae) from the Pearl River drainage in southern China - Tan, Xi-Chang; Li, Peng; Wu, Tie-Jun; Yang, Jian (Zootaxa, 2019)
A new spined loach of the genus Cobitis Linnaeus is described from the Buquan River, located in Guangxi Zhuang Autonomous Region, China. The species differs from other members of Cobitis in China by a combination of morphological characters, none of them unique: body depth 14.3‒18.4% SL; lamina circularis long and knife-shaped; Gambetta zones present on the dorsolateral sides of the body (L1‒L5); 8‒11 large transverse elongated blotches on L5; 9‒12 large transverse elongated blotches on L1; maxillary barbels longer than eye diameter; 4‒5 narrow rows of dark spots on the caudal fin; caudal fin with 14 branched rays; a rectangular spot slightly smaller than eye diameter on the upper side of caudal fin base; and caudal-peduncle depth 79.5‒93.1% its length.